Examining the effects of trade liberalisation using a gravity model approach - Martina Basarac Sertić; Valentina Vučković; Ana Andabaka (Economics: The Open-Access, Open-Assessment Journal, 2024)
The main objective of this article is to study the impact of trade liberalisation in Croatia as one of the first structural reforms being implemented, covering the period from 2000 to 2021. The panel data model was specified using a two-step system generalised method of moment estimator. The obtained results show that trade liberalisation measured through the specific indices encompassing a broader set of both tariff and non-tariff barriers, size of the trade sector, freedom of foreign exchange market, and capital controls positively impacted export performance. The results also showed a negative and statistically significant effect of remoteness on trade, confirming that geographical distance is an essential indicator of transportation costs. The coefficient for Schengen accession was positive and statistically significant, indicating that the Schengen agreement has boosted exports and that we can expect the same for Croatia, especially in the context of simultaneous accession to the Eurozone and the Schengen area on 1 January 2023.
Keywords: F43; F53; F62; 330; international trade; European Union; Schengen; Croatia; GMM